A Five-Country Survey on Ethics Education in Preservice Teaching Programs. (March 2016) - Maxwell, Bruce; Tremblay-Laprise, Audrée-Anne; Filion, Marianne; Boon, Helen; Daly, Caroline; van den Hoven, Mariette; Heilbronn, Ruth; Lenselink, Myrthe; Walters, Sue
Despite a broad consensus on the ethical dimensions of the teaching profession, and long-standing efforts to align teacher education with wider trends in professional education, little is known about how teacher candidates are being prepared to face the ethical challenges of contemporary teaching. This article presents the results of an international survey on ethics content and curriculum in initial teacher education (ITE). Involving five Organisation for Economic Co-Operation and Development (OECD) countries—the United States, England, Canada, Australia, and the Netherlands—the study's findings shed light on teacher educators' perspectives on the contribution of ethics content to the education of future teachers and provide a snapshot of how well existing programs line up with their aspirations. The results showed that 24% of the ITE programs surveyed contain at least one mandatory stand-alone ethics course. The meaning of the results vis-à-vis opportunities for expanding ethics education in preservice teaching programs is also discussed.